Formação inicial de professores em Educação Física pelo PARFOR no Estado de Roraima: diálogo com egressos - (:unkn) unknown (Universidade Federal do Amazonas, 2021)
The object of the present study was the initial training of teachers in Physical Education through the National Training Plan for Teachers of Basic Education - PARFOR. Focusing on the experience of the Degree Course in Physical Education offered by the Federal Institute of Education, Science and Technology of Roraima. We start from the assumption that training policies have been less concerned with the democratization and access to knowledge, and more with expanding quantitatively the training, even in conditions of impoverished qualities, developing training policies and reforms that are increasingly fragmented and lightweight. We sought to find out the perception that graduates of the first degree in Physical Education from IFRR/PARFOR in Rorainópolis have about their initial training, particularly about the reverberations of this experience in their pedagogical practice/professional action. Therefore, the general objective was to analyze the contribution of the initial training in the professional development of Physical Education teachers graduating from the first Physical Education degree of IFRR/PARFOR of Rorainópolis. To support this thesis, the concepts of initial training, teacher development and pedagogical practice were discussed, based on authors such as Freire (1987, 1991, 1996), Nóvoa (1992, 1999, 2009), Imbernón (2009; 2011), Pimenta (2012), Contreras (2002), André (2002; 2010), Gutierrez (1972), Castellani Filho (2001), Darido (2003), Soares (2007), Betti (2013), among others. Starting from the methodological principles of a qualitative research, the empirical data were produced, using different instruments of approach, such as the documental analysis of the course curriculum and documents that govern the PARFOR for a better understanding of the object; the semi-structured questionnaire; interviews with the egresses, observation and field diary, and photographic records. The participating subjects were former teachers of a first degree class that was offered in the municipality of Rorainópolis-RR in the period from 2011 to 2015. The data were analyzed based on prose analysis, as proposed by André (1983) and Nascimento (2019). The research participants reported that the training significantly influenced the way of being-knowing-doing, however, it was possible to identify practices without theoretical support, fragmented specific knowledge, difficulty of theoretical-practical articulation and disconnection of research in the teaching work, evidencing a technical-practical training model. The access to training through PARFOR has contributed significantly to raise the level of teacher training in Amazonian contexts, especially for training in Physical Education, reaching the most remote and less privileged areas of the country. However, the findings of the study reveal gaps and highlight the criticisms that are made by graduates about their training from the view of incompleteness, as they recognize and point out the continuing education that addresses the regional contexts and particularities, a permanent need.

El presente estudio tuvo como objeto de investigación la formación inicial de docentes en Educación Física a través del Plan Nacional de Formación Docente de Educación Básica - PARFOR. Centrándonos en la experiencia de la Licenciatura en Educación Física que ofrece el Instituto Federal de Educación, Ciencia y Tecnología de Roraima. Suponemos que las políticas de formación se han preocupado menos por la democratización y el acceso al conocimiento, y más por la ampliación cuantitativa de la formación, incluso en condiciones de empobrecimiento, desarrollando políticas y reformas formativas cada vez más fragmentadas y aligeradas. Se buscó conocer qué percepción tienen los egresados del primer grado en Educación Física de la IFRR / PARFOR en Rorainópolis sobre su formación inicial, en particular, sobre las reverberaciones de esta experiencia en su práctica pedagógica / práctica profesional. Por lo tanto, se eligió como objetivo general, analizar la contribución de la formación inicial en el desarrollo profesional de los docentes de Educación Física egresados del primer Grado de Física en IFRR / PARFOR en Rorainópolis. Para sustentar esta tesis, se buscó discutir los conceptos de formación inicial, desarrollo docente y práctica pedagógica, apoyándonos en autores como Freire (1987, 1991, 1996), Nóvoa (1992, 1999, 2009), Imbernón (2009; 2011), Pimenta (2012), Contreras (2002), André (2002; 2010), Gutiérrez (1972), Castellani Filho (2001), Darido (2003), Soares (2007) Betti (2013), entre otros. A partir de los principios metodológicos de una investigación cualitativa, se produjeron datos empíricos, utilizando distintos instrumentos de abordaje, como el análisis documental del currículo del curso y los documentos que rigen PARFOR para una mejor comprensión del objeto; el cuestionario semiestructurado; entrevistas a egresados, observación y diario de campo, además de registros fotográficos. Los sujetos participantes fueron docentes egresados de una promoción de primer grado que se ofreció en la ciudad de Rorainópolis-RR de 2011 a 2015. Los datos fueron analizados con base en el análisis en prosa, propuesto por André (1983) y Nascimento (2019). Los participantes de la investigación informaron que la formación influyó significativamente en la forma de ser-saber-hacer, sin embargo, fue posible identificar prácticas sin sustento teórico, conocimientos específicos fragmentados, dificultad en la articulación teórico-práctica y disociación de la investigación en la labor docente, mostrando un modelo técnico -entrenamiento practico. El acceso a la formación a través de PARFOR ha contribuido significativamente a elevar el nivel de formación docente en contextos amazónicos, especialmente para la formación en Educación Física, llegando a las zonas más remotas y menos privilegiadas del país. Sin embargo, los hallazgos del estudio revelan lagunas y resaltan las críticas de los egresados sobre su trayectoria formativa desde la perspectiva de la incompletitud, ya que reconocen y apuntan a una formación continua que contempla contextos y particularidades regionales, una necesidad permanente.
The initial training of teachers in Physical Education through the National Training Plan for Teachers of Basic Education - PARFOR.
Keywords: Professores - Formação; Educação física (Educação Básica); Rorainópolis (RR); Prática pedagógica; Professores de educação física; CIÊNCIAS HUMANAS; Formação Inicial; Educação Física; PARFOR; Desenvolvimento docente; Prática pedagógica